2012
DOI: 10.3109/19396368.2012.743198
|View full text |Cite
|
Sign up to set email alerts
|

The effect of molybdenum on thein vitrodevelopment of mouse preimplantation embryos

Abstract: The object of this study was to investigate the effect of molybdenum on the development of mouse preimplantation embryos cultured in vitro. Zygotes were flushed from one outbred mouse strain (Kunming), and then were cultured in potassium simplex optimized medium (KSOM) containing 0, 5, 10, 20, 40, 80, 120, and 160 µg/ml of molybdenum for 5 days until the midblastocyst stage. The addition of ≤ 20 µg/ml molybdenum did not affect the blastocyst and birth rates. Molybdenum at doses of 40 µg/ml and higher signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Molybdenum is very toxic to ruminants at levels of several parts per million being the most affected are cows (Underwood 1979;Kincaid 1980). Molybdenum toxicity in inhibiting spermatogenesis and arresting embryogenesis in organisms such as catfish and mice at levels as low as several parts per million have been reported (Meeker et al 2008;Bi et al 2013;Zhai et al 2013;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum is very toxic to ruminants at levels of several parts per million being the most affected are cows (Underwood 1979;Kincaid 1980). Molybdenum toxicity in inhibiting spermatogenesis and arresting embryogenesis in organisms such as catfish and mice at levels as low as several parts per million have been reported (Meeker et al 2008;Bi et al 2013;Zhai et al 2013;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum is commonly used in the industry and causes many instances of water poisoning worldwide such as in Malaysia [3], the Tokyo Bay, Tyrol in Austria and the Black Sea [4,5]. Toxicity to molybdenum has been recorded as low as a few parts per million resulting in the inhibition of spermatogenesis and embryonic in a number of species including catfish and mouse [6,[6][7][8][9]. In addition, molybdenum is extremely poisonous This work is licensed under the terms of the Creative Commons Attribution (CC BY) (http://creativecommons.org/licenses/by/4.0/).…”
Section: Introductionmentioning
confidence: 99%
“…This discovery came about during that decade. It has been demonstrated that even at concentrations as low as a few parts per million, molybdenum may inhibit the development of embryos and delay the process of spermatogenesis in various species, including catfish and mice [6,[6][7][8][9]. In addition, molybdenum is extremely hazardous to ruminants, particularly cows, at levels of several parts per million.…”
Section: Introductionmentioning
confidence: 99%